La biodégradation des feuilles du roseau commun par les bactéries (Phragmites australis) - BOUICH, NORIA; BOUCEDRA, DJAHIDA (My University, 2019)
The study of biodegradation of reed is widely explored because of their long life in nature, microbial colonization and its relationship with the biodegradation of common reed (Phragmites australis), the chemical compound supports growth and serves as a source of carbon and energy to microorganisms, and then biodegradation will occur only in the presence of the natural inducer. This can severely limit the applications of the enzymatic capacity. The main objective of this study was to isolate and identify bacteria used for the degradation of dead leaves of reed. This enabled us to identify and characterize two strains of Pseudomenas.
Keywords: Biodegradation; Phragmites australis; Pseudomenas; biofilm